2002
DOI: 10.1111/j.1945-5100.2002.tb00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectra of extremely reduced assemblages: Implications for Mercury

Abstract: — We investigate the possibility that Mercury's crust is very reduced with FeO concentrations of less than ˜0.1 wt%. We believe that such a surface could have a composition of enstatite, plagioclase, diopside, and sulfide, similar to the mineral assemblages found in aubritic meteorites. To test this hypothesis, we investigated the spectra of aubrites and their constituent minerals as analogs for the surface of Mercury. We found that some sulfides have distinctive absorption features in their spectra shortwards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 61 publications
9
86
1
Order By: Relevance
“…Such a huge amount of oldhamite on the Steins' surface is quite surprising, due to the fact that the percentage of sulfide oldhamite found in aubrite samples is smaller than 1% (Burbine et al, 2002b). Nevertheless, it is well known that oldhamite is extremely unstable in terrestrial conditions, and we cannot exclude that the abundance of oldhamite in aubrite materials and/or on the surface of the aubrite parent bodies might actually be larger than the one detected in terrestrial laboratory (Clark et al 2004;Burbine et al, 2002b).…”
Section: Accepted M Manuscriptmentioning
confidence: 84%
See 1 more Smart Citation
“…Such a huge amount of oldhamite on the Steins' surface is quite surprising, due to the fact that the percentage of sulfide oldhamite found in aubrite samples is smaller than 1% (Burbine et al, 2002b). Nevertheless, it is well known that oldhamite is extremely unstable in terrestrial conditions, and we cannot exclude that the abundance of oldhamite in aubrite materials and/or on the surface of the aubrite parent bodies might actually be larger than the one detected in terrestrial laboratory (Clark et al 2004;Burbine et al, 2002b).…”
Section: Accepted M Manuscriptmentioning
confidence: 84%
“…Nevertheless, it is well known that oldhamite is extremely unstable in terrestrial conditions, and we cannot exclude that the abundance of oldhamite in aubrite materials and/or on the surface of the aubrite parent bodies might actually be larger than the one detected in terrestrial laboratory (Clark et al 2004;Burbine et al, 2002b).…”
Section: Accepted M Manuscriptmentioning
confidence: 97%
“…On this basis, it has been suggested that hollow-formation involves the loss of the 'darkening' agent within LRM [Blewett et al, 2013], which may be spectrally neutral (making LRM relatively 'blue' by counteracting the 'redness' of other components) [Blewett et al, 2009]. Calcium or magnesium sulfides are most commonly-cited as candidates for the relatively volatile substance [Blewett et al, 2011[Blewett et al, , 2013Helbert et al, 2012], on the basis of the high concentration of sulfur detected at Mercury's surface [Nittler et al, 2011;Evans et al, 2012], expectations for mineralogy under Mercury's highly reducing conditions [Burbine et al, 2002], and correlations between sulfur, calcium and magnesium abundance in heavily-cratered terrains [Weider et al, 2015]. This hypothesis has recently gained further support from observations of anomalously high exospheric calcium above the extensively-hollowed Tyagaraja crater [Bennett et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…This observational technique, which utilizes the wavelength region from ~0.7-2.5-µm, is the main technique used to remotely study Mercury, Earth's Moon, and small solar system bodies such as the main-belt asteroids (e.g., Gaffey et al, 1993;Pieters et al, 2000;Burbine et al, 2002;Vernazza et al, 2010;Clark et al, 2011;Emery et al, 2011;Reddy et al, 2011;Lindsay et al, 2013;Rivkin et al, 2013). This technique is useful because it focuses on the spectral region where an object's primary surface mineralogy usually dominates over secondary effects, such as grain size variations, space weathering, observational variables, etc.…”
Section: Goal 2 -Mineralogical Characterization Of V P -Type Asteroidsmentioning
confidence: 99%